Use of Sodium Diethyldithiocarbamate to Enhance the Open‐Circuit Voltage of CH3NH3PbI3 Perovskite Solar Cells. Issue 4 (17th February 2021) - Más-Montoya, Miriam; Curiel, David; Wang, Junke; Bruijnaers, Bardo J.; Janssen, René A. J.
Abstract : The incorporation of additives to modulate the properties of metal halide perovskite thin films has become a successful approach in improving the power conversion efficiency of perovskite‐based solar cells. Herein, the beneficial use of sodium diethyldithiocarbamate (NaDEDTC) as processing agent in improving the open‐circuit voltage of methylammonium lead triiodide perovskite solar cells is reported. DEDTC reduces the rate of perovskite crystallization. Absorption and emission spectra show that the optical bandgap of the perovskite films remain essentially unchanged and X‐ray diffraction reveals the formation of preferentially oriented crystallites independent of the use of DEDTC. The use of DEDTC, however, results in a decrease in nonradiative decay as inferred from a two order of magnitude increase in electroluminescence efficiency, explaining the increased open‐circuit voltage. Fourier‐transform infrared spectroscopy, nuclear magnetic resonance, and X‐ray photoelectron spectroscopy show that the DEDTC ligand is not present after the film processing. Therefore, DEDTC modulates film formation but is not incorporated in the perovskite or present as a surface ligand. Sodium ions, on the contrary, are incorporated in the perovskite layer. Abstract : Sodium diethyldithiocarbamate (NaDEDTC) as processing agent enhances the open‐circuit voltage of methylammonium lead triiodide perovskite solar cells. DEDTC modulates film formation, improves the charge transfer between the hole transporting layer and the perovskite, and reduces nonradiative recombination. However, it is not incorporated in the perovskite or present as a surface ligand.